PENGARUH PENDAPATAN ORANG TUA DAN LITERASI KEUANGAN TERHADAP PERILAKU MANAJEMEN KEUANGAN SANTRI DI PONDOK PESANTREN MUROTALUL QUR’AN NURUL HUDA TASIKMALAYA - Ariska Meilinda; Heidi Siddiqa; Sri Sudiarti (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2025)
This study examines the effect of parental income and financial literacy on the financial management behavior of students (santri) at the Murotalul Qur’an Nurul Huda Islamic Boarding School in Tasikmalaya. The research was motivated by unstable saving behavior among students, indicating inconsistent financial management. Using a quantitative explanatory approach, data were collected from 145 respondents through questionnaires and analyzed using multiple linear regression. The results show that both parental income and financial literacy significantly influence students’ financial management behavior, with an R² value of 0.64. Financial literacy is the dominant factor, meaning students with higher financial knowledge tend to plan, save, and manage their spending better. Parental income supports financial stability but is not the sole determinant of behavior. The study concludes that financial education integrated with Islamic values is essential to build responsible and sustainable financial habits among students.